An altered gut microbiome in pre-eclampsia: cause or consequence - Deady, Clara; McCarthy, Fergus P.; Barron, Aaron; McCarthy, Cathal M.; O’Keeffe, Gerard W.; O’Mahony, Siobhain M. (Frontiers in Cellular and Infection Microbiology, 2024)
Hypertensive disorders of pregnancy, including pre-eclampsia, are a leading cause of serious and debilitating complications that affect both the mother and the fetus. Despite the occurrence and the health implications of these disorders there is still relatively limited evidence on the molecular underpinnings of the pathophysiology. An area that has come to the fore with regard to its influence on health and disease is the microbiome. While there are several microbiome niches on and within the body, the distal end of the gut harbors the largest of these impacting on many different systems of the body including the central nervous system, the immune system, and the reproductive system. While the role of the microbiome in hypertensive disorders, including pre-eclampsia, has not been fully elucidated some studies have indicated that several of the symptoms of these disorders are linked to an altered gut microbiome. In this review, we examine both pre-eclampsia and microbiome literature to summarize the current knowledge on whether the microbiome drives the symptoms of pre-eclampsia or if the aberrant microbiome is a consequence of this condition. Despite the paucity of studies, obvious gut microbiome changes have been noted in women with pre-eclampsia and the individual symptoms associated with the condition. Yet further research is required to fully elucidate the role of the microbiome and the significance it plays in the development of the symptoms. Regardless of this, the literature highlights the potential for a microbiome targeted intervention such as dietary changes or prebiotic and probiotics to reduce the impact of some aspects of these disorders.